If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + (2 + -4c) + -2 = 0 Remove parenthesis around (2 + -4c) c + 2 + -4c + -2 = 0 Reorder the terms: 2 + -2 + c + -4c = 0 Combine like terms: 2 + -2 = 0 0 + c + -4c = 0 c + -4c = 0 Combine like terms: c + -4c = -3c -3c = 0 Solving -3c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-3'. c = 0 Simplifying c = 0
| 2x^2+17x+26=0 | | 10x-73=73 | | 1x+11+1x=43 | | y=140+-0.7x | | -5*-10= | | 2m-21m=9m+7 | | 12(-7)-28=-63+7(-7) | | -7n-37=-3(8n-5)-1 | | -(-46x)=0 | | 17p+p=40-2p | | 1.33x=8 | | y=0.7(200-x) | | 6x-5=5(x-3)+x | | 7u-2u=3u+22 | | 2x^2+31x+110=0 | | -4.5c=-27 | | 4x^2+27x+-12=0 | | X+11+x=43 | | 2.4z=-24 | | 13d+25=8d | | 1.5b-16=8 | | 99+6u=-3u | | 0.03(x-40)+0.9(x+10)=45 | | -4x-10x=25 | | -(-6)=6x | | 12-9w=75 | | -64=-15m-4 | | 9x=2x+14 | | 8x+63+20+x=-61 | | -11=61-6q | | 3(d-1)+4=-2d | | 90=10p-90 |